Disconnected – Impaired Interoceptive Accuracy and Its Association With Self-Perception and Cardiac Vagal Tone in Patients With Dissociative Disorder - Schäflein, Eva; Sattel, Heribert C.; Pollatos, Olga; Sack, Martin (Frontiers in Psychology, 2018)
Patients suffering from dissociative disorders are characterized by an avoidance of aversive stimuli. This includes the avoidance of emotions and, in particular, bodily perceptions. In the present pilot study, we explored the potential interoceptive accuracy deficit of patients suffering from dissociative disorders in a heartbeat detection task. Moreover, we investigated the impact of facial mirror-confrontation on interoceptive accuracy and the potential association between cardiac vagal tone derived from heart rate variability and interoceptive accuracy. Eighteen patients suffering from dissociative disorders and 18 healthy controls were assessed with the Mental Tracking Paradigm by Schandry for heartbeat detection at baseline and after confrontations exposing them to their own faces in a mirror (2 min each, accompanied by a negative or positive cognition). During the experiment, cardiac vagal tone was assessed. We used Pearson correlations to calculate potential associations between cardiac vagal tone and interoceptive accuracy. Patients performed significantly worse than the healthy controls in the heartbeat detection task at baseline. They displayed no significant increase in interoceptive accuracy following facial mirror-confrontation. In the patient group, higher cardiac vagal tone was associated with a more precise heartbeat detection performance. Dissociative disorder patients showed a considerable deficit in interoceptive accuracy. Our results fit with the assumption that highly-dissociative patients tend to tune out the perceiving of bodily signals. To the extent that bodily signal perception may play a causal role in these disorders, therapeutic approaches enhancing interoceptive accuracy and cardiac vagal tone may be considered important and practicable steps to improve the therapy outcome of this patient group.